Biogas production from Palm Oil Mill Effluent (POME) using mono- and co-digestion with pilot-scale Integrated Anaerobic-Aerobic Bioreactor (IAAB) - Yap, Cheau Chin (2021)
In the preliminary stage, start-up, long-term performance evaluation [organic loading rate (OLR) 10.5 gCOD/L.day to 32.5 gCOD/L.day] and kinetic analysis of the pilot-scale IAAB were conducted at mesophilic condition (28°C). Based on the performance studies of the pilot-scale IAAB at different OLRs, the maximum applicable OLRan at which mesophilic system could maintain steady state operation was at OLRan 30.0 gCOD/L.day. The quality of the final treated effluent remained stable with high percent of compliance with the discharge limit of 100 mg/L. Modified Stover Kincannon, Grau second-order and Monod kinetic models were applied to the pilot-scale IAAB at OLRan 10.5 - 32.0 gCOD/L.day. It was concluded that Stover Kincannon model is the most appropriate model to estimate the performance of the anaerobic (R2 of 0.9982) and aerobic systems of the pilot-scale IAAB (R2 of 0.9998).